The Demand for Money: Theories and Evidence - Minsky, Hyman P.; Laidler, David E. W. (Econometrica, 1972)
The Demand For Money: Theories and Evidence , The Demand For Money: Theories and Evidence , کتابخانه دیجیتال و فن آوری اطلاعات دانشگاه امام صادق(ع)